Behavioural and nondirective parent training for children with externalising disorders: First steps towards personalised treatment recommendations. (April 2023) - Hautmann, Christopher; Dose, Christina; Hellmich, Martin; Scholz, Kristin; Katzmann, Josepha; Pinior, Julia; Gebauer, Stephanie; Nordmann, Lisa; Wolff Metternich-Kaizman, Tanja; Schürmann, Stephanie; Döpfner, Manfred
Abstract: For children with externalising disorders, parent training programmes with different theoretical foundations are available. Currently, there is little knowledge concerning which programme should be recommended to a family based on their individual needs (e.g., single parenthood). The personalised advantage index (PAI) indicates the predicted treatment advantage of one treatment over another. The aim of the present study was to examine the usefulness of this score in providing individualised treatment recommendations. The analysis considered 110 parents (per-protocol sample) of children (4–11 years) with attention-deficit/hyperactivity (ADHD) or oppositional defiant disorder (ODD), randomised to either a behavioural or a nondirective telephone-assisted self-help parent training. In multiple moderator analyses with four different regression algorithms (linear, ridge, k-nearest neighbors, and tree), the linear model was preferred for computing the PAI. For ODD, families randomised to their PAI-predicted optimal intervention showed a treatment advantage of d = 0.54, 95% CI [0.17, 0.97]; for ADHD, the advantage was negligible at d = 0.35, 95% CI [–0.01, 0.78]. For children with conduct problems, it may be helpful if the PAI includes the treatment moderators single parent status and ODD baseline symptoms when providing personalised treatment recommendations for the selection of behavioural versus nondirective parent training. Trial registration: The study was registered prospectively with ClinicalTrials.gov (Identifier NCT01350986). Highlights: Behavioural and nondirective parent training programmes are available. Personalised advantage index (PAI) for individual treatment recommendations. For symptoms of oppositional defiant disorder, the PAI may be helpful. For attention-deficit/hyperactivity disorder symptoms, the PAI provides a negligible advantage. Prospective trials are needed to validate the use of the PAI.